Real will of the people in the pretended bargains - Скиданов, К. В. (Theory and practice of jurisprudence, 2016)
The article is devoted to defining the characteristics and differences of the imaginary and the sham transactions. Determined by the nature of defects will the perpetrators of such transactions, and the reasons for their recognition by the court invalidated. Analyzes on materials 12 legal ways of proving violations on the parties to the transaction reaching a certain goal. Attention is paid to the consequences of invalidity of fictitious and imaginary transactions.